Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41467-019-12563-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of multidrug resistant bacteria on intensive care unit surfaces

Abstract: Bacterial pathogens that infect patients also contaminate hospital surfaces. These contaminants impact hospital infection control and epidemiology, prompting quantitative examination of their transmission dynamics. Here we investigate spatiotemporal and phylogenetic relationships of multidrug resistant (MDR) bacteria on intensive care unit surfaces from two hospitals in the United States (US) and Pakistan collected over one year. MDR bacteria isolated from 3.3% and 86.7% of US and Pakistani surfaces, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 93 publications
3
45
0
Order By: Relevance
“…The most common external perturbations to the microbiome are diet, medications (especially antibiotics), and the environment [26][27][28][29][30][31]. In this review, we focus on antibiotic perturbation throughout life and associations with other factors including age and maturity of the microbiome, diet and the environment, and the co-morbidities of the individual (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The most common external perturbations to the microbiome are diet, medications (especially antibiotics), and the environment [26][27][28][29][30][31]. In this review, we focus on antibiotic perturbation throughout life and associations with other factors including age and maturity of the microbiome, diet and the environment, and the co-morbidities of the individual (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Through core genome phylogenetic analysis, we found that our CRAB isolates are dominated by single lineage. Previous report of A. baumannii and E. faecium isolates from Pakistan and the USA hospital system showed they were similarly dominated by single lineages (D'Souza et al, 2019). Contrastingly, these strains were composed of three clusters and eight clones.…”
Section: Discussionmentioning
confidence: 80%
“…Plates were incubated at 35°C under aerobic conditions (except in the case of anaerobic brucella blood agar) for 14 h. Individual bacterial colonies from the selective media were identified by MALDI-TOF MS (bioMérieux Vitek MS), and antimicrobial susceptibility testing (AST) was performed using Kirby-Bauer disk diffusion and interpreted using CLSI standards. DNA extraction was performed as previously described ( 28 ). C. difficile was cultured anaerobically and isolated (with ribotyping and toxin gene detection performed) as previously described ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Library preparation and sequencing of metagenomes and isolate genomes. Illumina libraries of fecal metagenomic DNA, C. difficile isolate DNA, and VRE isolate DNA were prepared as described previously (28,31). Reads for both metagenomes and isolate genomes were processed and filtered as described previously (Text S1) (28,32).…”
Section: Methodsmentioning
confidence: 99%